PERBEDAAN EFEKTIVITAS MCKENZIE EXERCISE DENGAN PEMBERIAN EDUKASI TERHADAP FORWARD HEAD POSTURE PADA MAHASISWA POLTEKKES KEMENKES JAKARTA III - Kurniawan, Ganesa Puput Dinda; Risyaputri, Kirana Fitria; Sariana, Erna (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Background: Long-term use of smartphones in adolescents can have a negative impact on the body such as Forward Head Posture. Forward Head Posture is a musculoskeletal disorder in the form of an abnormal posture in the neck area. One of the interventions that can be use is the McKenzie Exercise. McKenzie Exercise is a repetitive exercise that focuses on extension movements, which includes Range of Motion (ROM) and manipulation exercises. As well as providing education to sufferers about how to have good and ergonomic posture of the curve on Forward Head Posture. Methods: This research is a quasi experimental design with two group pretest posttest. The sample was selected by purposive sampling method with a total 24 people, 12 people in Group A that given McKenzie Exercise dan 12 others in Group B that given education. Result: The Mann-Whitney Test was used to analyzed pre-test and post-test differences in McKenzie Exercise Group (mean 16,63) and Educational group (mean 8,38) on Forward Head Posture (p=0,004). Conclusion: There is a difference in influence between the group A and the group B.